2016
DOI: 10.1159/000453139
|View full text |Cite
|
Sign up to set email alerts
|

MiR-181a Targets PHLPP2 to Augment AKT Signaling and Regulate Proliferation and Apoptosis in Human Keloid Fibroblasts

Abstract: Background/Aims: Keloids are fibrous overgrowths induced by cutaneous injury. MicroRNAs (miRNAs) have recently emerged as post-transcriptional gene repressors and participants in a diverse array of pathophysiological processes leading to skin disease. The purpose of the current study was to explore the precise functions of miR-181a in human keloid development and the underlying mechanisms. Methods: A miRNA microarray analysis was performed to compare expression profiles between keloid and normal skin tissues. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
48
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 21 publications
0
48
0
Order By: Relevance
“…miRNA may play a crucial role in the pathogenesis of keloid . The miRNA expression profiles in keloid scarring have been investigated by previous studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…miRNA may play a crucial role in the pathogenesis of keloid . The miRNA expression profiles in keloid scarring have been investigated by previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Certain miRNAs have been considered to be common regulators in keloid via their relevant target genes . The expression level of miRNA‐199a was lower in the keloid tissue compared to the normal sample.…”
Section: Discussionmentioning
confidence: 99%
“…Human miR-181a and miR-181b genes are clustered together and located on two chromosomes, 1 and 9, whereas miR-181c and miR-181d genes are clustered together on chromosome 19 [8, 9]. Recent studies have reported the involvement of miR-181a in diverse cellular functions such as growth, proliferation, death, survival, and maintenance, as well as tumor suppression and carcinogenesis [10, 11]. Though some studies have shown that miR-181a expression is downregulated in several human solid tumors [12-17], others have demonstrated that upregulation of miR-181a may promote metastasis and invasion of human cancers [18-20].…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNAs (miRNAs), a class of non-coding RNAs with approximately 18-25 nucleotides, are involved in various aspects of cellular functions such as cell proliferation, differentiation, migration, and apoptosis [4][5][6]. Increasing evidence has shown that miRNAs play a vital role in drug resistance [7,8], which leads to treatment failure in cancer.…”
Section: Introductionmentioning
confidence: 99%